In Search of the “Bright Side of Life“. Adolescence, Love and Emancipation in Eduard von Keyserling’s Novel Fräulein Rosa Herz - Orozović, Anja (Anafora, 2025)
Eduard von Keyserling’s first novel, Fraulein Rosa Herz (1887), was not a bestseller. The researcher’s negligent attitude towards Keyserling’s early work is unsurprising, given that he later distanced himself from it. However, the novel provides a significant insight into Keyserling’s poetics as it addresses a variety of time-specific topics, including adolescence. Notably, Keyserling’s writing generally pays more attention to the female experience of adolescence. This paper addresses the individual problem points related to this topic. The publication of Fraulein Rosa Herz in the 1980s makes it difficult to categorize it as an adolescent novel; nonetheless, it can be viewed as an interesting and valuable contribution to modernist literature for adolescents.